2012
DOI: 10.1371/journal.pone.0052412
|View full text |Cite
|
Sign up to set email alerts
|

Limited Relationship between Cervico-Vaginal Fluid Cytokine Profiles and Cervical Shortening in Women at High Risk of Spontaneous Preterm Birth

Abstract: ObjectiveTo determine the relationship between high vaginal pro-inflammatory cytokines and cervical shortening in women at high risk of spontaneous preterm labor and to assess the influence of cervical cerclage and vaginal progesterone on this relationship.MethodsThis prospective longitudinal observational study assessed 112 women with at least one previous preterm delivery between 16 and 34 weeks’ gestation. Transvaginal cervical length was measured and cervico-vaginal fluid sampled every two weeks until 28 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 33 publications
3
46
0
Order By: Relevance
“…This finding was also described by Matoba et al who quantified twenty-seven types of cytokines in cord blood at different gestational ages and found that MCP-1 was the one that was most strongly associated with PTB [40]. Significantly higher levels of MCP-1 have also been measured in cervicovaginal fluid [41] …”
supporting
confidence: 82%
“…This finding was also described by Matoba et al who quantified twenty-seven types of cytokines in cord blood at different gestational ages and found that MCP-1 was the one that was most strongly associated with PTB [40]. Significantly higher levels of MCP-1 have also been measured in cervicovaginal fluid [41] …”
supporting
confidence: 82%
“…Samples for AMP analysis were obtained from a subset of women recruited to a previously reported prospective observational study (the C ervical L ength and I nflammatory C hanges: CLIC study) [23] designed to assess the relationship between inflammation and cervical shortening in women at high risk (i.e. women with a previous history or late miscarriage or sPTB) of sPTB.…”
Section: Methodsmentioning
confidence: 99%
“…Cervical length was assessed in accordance with standardised guidelines [23]. In brief, a sagittal view of the cervix was obtained with the long axis view of the echogenic endocervical mucosa along the length of the canal, allowing identification of both the internal and external os.…”
Section: Methodsmentioning
confidence: 99%
“…Several proinflammatory cytokines such as interleukin (IL)-1, IL-6, IL-8 and TNFα, have been detected in cervico-vaginal fluid in women at high risk of sPTB and women in threatened preterm labour [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%